Filsafat Ilmu Menurut al-Qurâan - Solehudin, Ending (Program Pascasarjana UIN Sunan Ampel Surabaya, 2012)
Three decades ago, philosophy as an object of investigation was still unlawful religiously among the santris and even among some Muslim university students in Indonesia. That is no longer the case now. Following the coming of some open-minded religious discourses in the country especially that which was brought about by a well-known scholar named Harun Nasution, the study of philosophy became lawful and even promising. This paper speaks about this phenomenon by looking at the evolution of the study of philosophy âespecially the philosophy of science- in the academic study in Indonesia. Within the framework of evolution theory, the paper also tries to discuss how the study of this science evolves from a sheer Western-based study to include the Qurâanic perspective of it. This paper itself is a study of the Qurâanic perspective concerning the philosophy of science. And by doing that, it tries to show that this kind of study has become a trend in academic circle in Indonesia.